If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z = 3x + -1y Solving z = 3x + -1y Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Simplifying z = 3x + -1y
| y=0.95x | | 9.2-x=7.3 | | -7x+y=-1 | | 3x-11=x-5 | | -3(2x-3)=3(x-6) | | 4x+3=2(2x+2)-2x | | y=0.75(4)x | | 4=-0.5x^2+46 | | 42=12+3p | | 31(2c+4)=2(c+6)+c | | 7[2e-1]-3=6+6e | | 32=7(n+7)+5(5n+3) | | Y+2=.6(x+4) | | 42=2.333333x | | 6x+34x=7 | | 10p-3=2[12+4p]-7 | | 800=2x+3x+10x | | 9g=3[-4+5g] | | 500=2x+8x | | Y=-.6x-1 | | 3j+10=-30 | | .13x+x=141 | | 4[3+c]+c=c+4 | | 400=2x+6x | | x^3+y^2+2y-4x=5 | | 3z^2-7x+2=0 | | 28=14+7x-42 | | 3x-2y+5z=16 | | 9(y+5)=y+45 | | 4[3+c]+4=c+4 | | 54.6=6(m+2.9) | | P=2(pi)*r+2x |